MODEL PERLINDUNGAN PREVENTIF BAGI KONSUMEN ONLINESHOP MELALUI KETERBUKAAN INFORMASI - Ukie Tukinah (UNISSULA, 2015)
Increasingly popular activity online transactions conducted in the era of technological sophistication, because it has many advantages that can reduce the cost of sale and also enable consumers to shop. However, there are drawbacks of online transactions, the absence of a meeting between businessmen and consumers and the limited access of consumers to examine and see first hand the goods to be purchased. This weakness that has not been optimally accommodated by the government where there are still gaps violations of consumer rights. The study analyzes the normative connectedness online entrepreneurs get their business license legality with consumer protection. But in the licensing business licensing are not regulated marketing system through online media (Onlineshop), but quite the online transaction activity has great potential cause pencideraan the rights of consumers. The results of this study indicate that there are no special arrangements for the business registration mechanism onlineshop and lack of public access to information related to the existence of businesses onlineshop. Thereby consumer protection model that made the researcher is a form of standardization of the provisions of indicators: (1) locus; (2) tempus; (3) the subject of law; (4) the type of products sold; (5) the type of marketing; (6) the necessity of special licenses for businesses that perform online marketing; and (7) should be no public disclosure of information so as to materialize. Standardization of this provision shall be submitted to the central government to be made a joint regulation of communications and information minister and trade minister.